Transfection of Escherichia coli spheroplasts. VI. Transfection of nonpermissive spheroplasts by T5 and BF23 bacteriophage DNA carrying amber mutations in DNA transfer genes. - Benzinger, R (1975)
DNA was extracted from T5 and BF23 phage carrying amber mutations in genes A2, A1, or D9 and tested for its ability to transfect su minus spheroplasts. DNA from T5 am231, defective in gene A2, transfects Escherichia coli su minus recB minus spheroplasts with an efficiency of 16% of that of wild-type T5 DNA, whereas DNA from T5 am16d or BF23 am57, both defective in gene A1 or its equivalent, transfects E. coli su minus recB minus spheroplasts with an efficiency of 1.4% of that of wild-type T5 DNA, provided E. coli su+ bacteria is used as the indicator in all cases. More than 95% of the progeny from the am231, am16d, and am57 DNA that transfects su minus recB minus spheroplasts is still amber mutant. From these efficiencies of transfection we conclude that the product of gene A2 functions mainly in the mechanism of transfer of phage DNA to intact host cells, and that this function is not essential for transfection of spheroplasts. We also conclude that gene A1 controls functions in addition to DNA transfer, in agreement with previous studies which show that mutations in gene A1 have a pleiotropic effect. Apparently, the absence of these additional functions controlled by gene A1 leads to a high frequency of abortive infection. DNA from amber mutants defective in either gene A1 or A2 does not appreciably transfect su minus rec+ spheroplasts, indicating that the products of these two genes may both be needed to protect T5 DNA from the very active rec BC nuclease in spheroplasts.